Emerging economies, trade policy, and macroeconomic shocks - Chad P. Bown; Meredith A. Crowley (Federal Reserve Bank of Chicago, 2012)
This paper estimates the impact of macroeconomic shocks on the trade policies of thirteen major emerging economies over 1989 - 2010; by 2010, these WTO member countries collectively accounted for 21 percent of world merchandise imports and 22 percent of world GDP. We examine determinants of carefully constructed, bilateral measures of new import protection imposed at the extensive margin. New import restrictions on products arise through the temporary trade barriers (TTBs) - antidumping, safeguards, and countervailing duties - that have become some of the most important time-varying trade policies in use. Our approach explicitly addresses changes to the institutional environment facing these emerging economies as they joined the WTO and promised to restrain other trade policies by keeping applied import tariffs below specified maximum levels. After controlling for this phenomenon, bilateral real exchange rate fluctuations, and potential differences across exchange rate regimes, we find general evidence of a counter-cyclical relationship between macroeconomic shocks and new import protection through TTBs. Furthermore, for the subset of major G20 emerging economies, the trade policy responsiveness coinciding with the onset of the WTO in 1995 through 2008 suggests a significant change relative to the pre-WTO period; i.e., import protection through these policy instruments became more countercyclical over time. Finally, we document evidence on potential changes to the channels through which macroeconomic shocks affect emerging economy new import protection coinciding with the timing of the Great Recession.
Keywords: F13; 330; antidumping; safeguards; temporary trade barriers; emerging markets